Development of High-Performance Engineered Textiles for Medical Applications: A Quality Function Deployment (QFD) Study - Irwanto, Miko Mei; Pane, Akhmad Fauzi; Wijayanti, Atiek Ike (Pt. Anagata Sembagi Education, 2026)
The rapid growth of biomedical applications and the increasing demand for advanced healthcare solutions have intensified the need for high-performance engineered textiles in medical contexts. These textiles must simultaneously fulfill stringent clinical, mechanical, biological, and regulatory requirements. This study aims to develop and analyze a Quality Function Deployment (QFD) framework to systematically translate clinical and user requirements into prioritized engineering specifications for medical textile development. A quantitative–descriptive approach was employed using stakeholder surveys, expert interviews, and literature analysis to identify the Voice of Customer (VoC). The House of Quality matrix was constructed to evaluate relationships between customer needs and technical characteristics. The results indicate that biocompatibility, mechanical durability, and antimicrobial performance are the highest-priority customer requirements. Correspondingly, fiber material composition, fabric structure, and surface functionalization emerged as the most critical technical characteristics. The discussion demonstrates that QFD effectively reduces overdesign, enhances cross-disciplinary alignment, and improves resource allocation in product development. In conclusion, QFD provides a structured and strategic framework for optimizing the development of high-performance medical textiles, ensuring alignment between clinical expectations and engineering feasibility while supporting innovation sustainability.